Signal Enhancement in Disperse Solutions for the Analysis of Biomedical Samples by Photothermal Spectroscopy - Proskurnin, M.A.; Volkov, D.S.; Ryndina, E.S.; Nedosekin, D.A.; Zharov, V.P. (ALT Proceedings, 2026)
Photothermal lens spectrometry not only shows high sensitivity of colored heme protein determination, but also provides a change in the sensitivity compared to the theoretical values due to changes in the heat transfer in dispersed media. This can be used for estimating the size of disperse particles exemplified by hemoglobin cyanide, photothermal examination of the state of existence of hemoglobin in highly saline solutions by changes in photothermal properties upon dissociation of hemoglobin tetramers into dimers and monomers. The example of determination of contrast agents (dyes) in blood as the versification of the platform of photoacoustic/photothermal measurement of circulating blood volume is shown.